Analyzing the influence of TOE factors on e-auditing adoption in audit firms: The moderating effect of trust - Reem Al-Araj (Decision Science Letters)
The rising usage of E-Auditing and its effect on businesses through new technology developments and rules demonstrates how audit systems can maximize operational efficiency and business decision quality. Researchers are undergoing a study to determine E-Auditing acceptance rates. The TOE model represents “Technological, Organizational, and Environmental” variables that function as key examination areas in organizational analysis and management practices when researchers study technological implementation and adoption patterns in industrial environments. The research proposes that these three aspects (technical aspects with both Relative advantage (RA) and Technology Compatibility (TC) and organizational aspects including top management support (TMS) and readiness (R)) along with environmental aspects such as competitive pressure (CP) contribute to e-auditing adoption. Auditor trust appeared in this study as the suggested moderating factor. A total of 235 participants provided info outside random sampling while the analysis used SPSS software. The experimental results proved that factors associated with TOE provide legitimate grounds for E-auditing acceptance. Evidence demonstrates that TOE variables provide justification for why organizations would accept E-auditing technology. Data show that trust functions as a supportive variable for the relationship between TOE and e-auditing but provides minimal strength. E-Auditing adoption research needs further investigation within emerging economies to understand better how users adopt this tool. The objective for decision-makers should focus on expanding user understanding of E-Auditing adoption along with educating decision-makers about the benefits of implementing this system.